CENTRIFUGATION METHODOLOGY TO EXTRACT SOIL SOLUTION - Somavilla, André; Dessbesell, Alexandre; Rheinheimer dos Santos, Danilo (Scientia Agraria, 2017)
The quantification of ions and compounds present in the soil solution is extremely difficult and requires standard extraction and quantification techniques. The present work describes in detail the equipment and procedures required to extract the soil solution by the centrifugation method of deformed soil samples and analyzes its application in soils with different granulometry. This description of centrifugation method and the Centrifuge 1.0 software are useful tools to author that desire a quickly and economically method to obtain the soil solution. We emphasize that there is no consensus on the best method of obtaining the soil solution, but is clear the need for the authors to explain how they obtained it.